PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL - Novitasari, Desy; Sarwono, Aris Eddy; Sunarti, Sunarti (Universitas Slamet Riyadi, 2019)
This study aims to find evidence about the factors that influence the allocation of capital expenditure budgets in the District and City Governments in Central Java Province. The factors tested in this study are regional own-source revenue, general allocation funds, and special allocation funds with control variables of total assets, surplus / devisit and a comparison between regional own-source revenue and total revenue. The samples in this study were all Regencies and Cities in Central Java Province or 29 Regencies and 6 Cities that issued local government financial reports that were audited by the Supreme Audit Board for the 2014 - 2017 period taken using the Purposive Sampling method. These factors were again tested using panel data regression at a significance level of 5 percent. The results of the study identified that the regional original income variable had no effect on the capital expenditure budget allocation, the general allocation fund variable had a significant positive effect on the capital expenditure budget allocation, while the special allocation fund variable had a significant positive effect on the capital expenditure budget allocation. With a control variable that affects only one, namely the number of assets.